An unusual case of systemic mastocytosis associated with chronic lymphocytic leukaemia (SM-CLL). Issue 3 (27th February 2006) - Horny, H-P; Sotlar, K; Stellmacher, F; Valent, P; Grabbe, J
Abstract : Aims: Whereas focal accumulations of reactive lymphocytes around mast cell (MC) infiltrates are often seen in indolent systemic mastocytosis (ISM) involving the bone marrow, an association of systemic mastocytosis (SM) with malignant lymphoma/lymphatic leukaemia is very rare. This report contributes to the differential diagnosis of ISM by demonstrating that such lymphocytic aggregates may be neoplastic. Methods: Biopsy specimens (bone marrow and gastrointestinal mucosa) of a 69 year old woman with mild blood lymphocytosis and a history of urticaria pigmentosa-like skin lesions that had disappeared a few years earlier, were investigated immunohistochemically using antibodies against CD3, CD5, CD20, CD23, CD25, CD34, CD117, chymase, and tryptase. Rearrangements of the IgH and TCRy genes were studied by seminested PCR. Mutation analysis of c- kit was performed by melting point analysis of nested PCR using amplified DNA from pooled microdissected single cells (MC and B cells) of both sites. Results: The histomorphological features of the bone marrow corresponded to that of ISM with multifocal accumulations of MC surrounded by clusters of lymphocytes of mature appearance. However, these lymphocytes revealed an aberrant immunophenotype with coexpression of CD5, CD20, and CD23, thus enabling the final diagnosis of SM with an associated clonal haematological non-MC lineage disease, in particular SM with associated B cell chronic lymphocytic leukaemia (SM-CLL). Monoclonality for both ISM and B-CLL could be confirmed by demonstrating the typical activating c-kit point mutation D816V in bone marrow MC, and a monoclonal IgH rearrangement in bone marrow B cells. Conclusions: Usually, focal accumulations of lymphocytes around MC infiltrates in the bone marrow of patients with SM are reactive in nature (lymphocytosis). However, a low grade malignant lymphoma should also be included in the differential diagnosis. We describe here the first case, to our knowledge, with synchronous diagnosis of SM and associated B-CLL. This diagnosis could only be established by application of appropriate immunohistochemical and molecular techniques, as the bone marrow histology on first investigation resembled that of typical ISM.